PROPOSED WORK STATION REPAIR AT PT DIAN ADI FURNI USING RANKED POSITIONAL WEIGHT METHOD (Science and Technology (SciTech), 2022)
This research was motivated by PT Dian Adi Furni who often experienced accumulation problems in the product completion process in the chair division. This is due to the high demand for Colonial seats in the area. The purpose of this study was to determine the efficiency of the initial production work station and to propose an optimal work station improvement by comparing the line balancing ranked positional weight (RPW) method. After the analysis, the initial work station has 6 work stations with a low line efficiency value of 40.62%, a high balance delay, which is 59.38% and a smoothness index value of 1073.7 seconds. The optimal work station improvement proposal was obtained from a cycle time experiment of 410.9 seconds which resulted in 4 work stations with a line efficiency (LE) of 97.95%, a balance delay (D) of 2.05% and a smoothness index of 492.17 seconds. .